Alterations of blood coagulation in controlled human malaria infection. (December 2016) - Riedl, Julia; Mordmüller, Benjamin; Koder, Silvia; Pabinger, Ingrid; Kremsner, Peter; Hoffman, Stephen; Ramharter, Michael; Ay, Cihan
Abstract Background Alterations of blood coagulation are thought to be involved in malaria pathogenesis. This study had the aim to investigate changes of blood coagulation under the standardized conditions of controlled human malaria infection. Methods In a clinical trial aseptic, purified, cryopreservedPlasmodium falciparum sporozoites were intravenously (n = 24) or intradermally (n = 6) injected into 30 healthy volunteers. Twenty-two participants developed parasitaemia. Serial blood samples before and during prepatent period and at parasitaemia, diagnosed by microscopic assessment of thick blood smear, were obtained. Biomarkers of blood coagulation (thrombin generation potential, D-dimer, prothrombin fragment 1 + 2, von Willebrand factor, ADAMTS13 activity and soluble P-selectin) were determined. Results At first detection ofP. falciparum parasitaemia, 72.7 % of volunteers had peak thrombin generation 10 % above their baseline. Overall, peak thrombin generation was 17.7 % higher at parasitaemia compared to baseline [median (25th–75th percentile): 225.4 nM (168.1–295.6) vs. 191.5 nM (138.2–231.9);p = 0.026 ]. There were no significant changes of other coagulation parameters. Conclusions The thrombin generation potential, an in vitro blood coagulation test, which reflects an individual´s global coagulation status, was increased by 17.7 % at very early stages ofP. falciparum malaria, suggesting a hypercoagulable state may be induced, even when parasite density is low.